2002
DOI: 10.1519/1533-4287(2002)016<0286:eoeate>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Exercise at Three Exercise Intensities on Salivary Cortisol

Abstract: Changes in cortisol concentration in response to exercise at 3 different intensities were quantified. Ten apparently healthy, recreationally active males participated. On 4 separate occasions, subjects were assigned a random order of 1-hour cycle ergometer bouts of exercise at 44.5 +/- 5.5%, 62.3 +/- 3.8%, and 76.0 +/- 6.0% (mean +/- SD) of VO2peak and a resting control session. Saliva samples were collected before exercise at 10, 20, 40, and 59 minutes of exercise and at 20 minutes of recovery. Differences in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
78
2
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(83 citation statements)
references
References 17 publications
2
78
2
1
Order By: Relevance
“…Unlike studies of the effect of exercise on cortisol in nonsmokers, which showed substantial increases in cortisol postexercise (Jacks et al 2002;McGuigan et al 2004), the current study noted decreases in cortisol levels from pre-to post-exercise in all conditions. This suggests that reductions in cortisol experienced by smokers on the first day of smoking abstinence may not be completely attenuated by exercise.…”
Section: Discussioncontrasting
confidence: 88%
“…Unlike studies of the effect of exercise on cortisol in nonsmokers, which showed substantial increases in cortisol postexercise (Jacks et al 2002;McGuigan et al 2004), the current study noted decreases in cortisol levels from pre-to post-exercise in all conditions. This suggests that reductions in cortisol experienced by smokers on the first day of smoking abstinence may not be completely attenuated by exercise.…”
Section: Discussioncontrasting
confidence: 88%
“…Plasma cortisol only increased in response to the 120-min run, whereas DHEA sulfate increased in a dose-response manner, with the greatest increases observed during the 120-min run. To our knowledge, only one study [20] compared the effects of several exercise intensities (44.5 ± 5.5%, 62.3 ± 3.8%, and 76.0 ± 6.0% of VO 2max ) on saliva cortisol response in healthy, recreationally active subjects during a 1-h submaximal trial. Saliva DHEA was not investigated, but the authors reported that saliva cortisol was significantly increased only at 76% VO 2max at the end of exercise.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, both intense and moderate levels of physical exercise acutely increase cortisol levels (Filaire, Duche, Lac, & Robert, 1996;Jacks, Sowash, Anning, McGloughlin, & Andres, 2002;Kindermann, Schnable, Schmitt, Biro, Cassens, & Webber, 1982;Tremblay, Copeland, & Van Helder, 2004). Studies examining change in cortisol secretion after extended training have equivocal results (Buyukyazi, Karamizrak, & Islegen, 2003;Lucia, Diaz, Hoyos, Fernandez, Villa, Bandres, & Chicharro, 2001), however most research on exercise and cortisol include relatively intense exercise protocols primarily among trained athletes.…”
Section: Nicolsonmentioning
confidence: 99%